Four graduates received VDI Karlsruhe Dual Degree Excellence Award - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 18 November – Four graduates under the collaboration program with Karlsruhe University Of Applied Sciences, Germany, were selected as the recipient for VDI Karlsruhe Dual Degree Excellence Award at the Universiti Malaysia Pahang (UMP) 12th Convocation Ceremony. They were Kong Zhung Jie and Usamah Shamsuddin graduates for Bachelor of Mechatronic (Hons), and Muhamad Hayat Mohd Nor and Syafiqah Nabilah Ahmad Salim graduates for Bachelor of Automotive Engineering.